About the relationship of rosacea-like dermatitis - Andrey L. Bakulev; Maria V. Bakuleva (State Scientific Center of Dermatovenereology and Cosmetology, 2023)
The literature review is devoted to the problem of rosacea-like dermatitis developing in patients with rosacea against the background of irrational uncontrolled use of topical glucocorticosteroids or cosmetics. The clinical picture of the combined pathology consists of symptoms characteristic of both diseases, which makes diagnosis difficult. Management tactics of patients with combined pathology, first of all, involves the elimination of symptoms of rosacealike dermatitis, dominating the clinical picture, using metronidazole, calcineurin inhibitors, azelaic acid, in severe cases low doses of systemic isotretinoin. The possibility of using activated zinc pyrithione, which has antimicrobial, anti-fungal and anti-inflammatory effects, as a topical remedy to eliminate the symptoms of rosacea-like dermatitis is discussed.